Shakespeare's Twenty-First Century economics : the morality of love and money - Turner, Frederick, 1943- (Oxford University Press, 1999)
Based on the proven maxim that "money makes the world go round", this study, drawing from Shakespeare's texts, presents a lexicon of common words as well as a variety of familiar familial and cultural situations in an economic context. Making constant recourse to well-known material from Shakespeare's plays, Turner demonstrates that terms of money and value permeate our minds and lives even in our most mundane moments. His book offers a new evolutionary economics that fully expresses the moral, spiritual, and aesthetic relationships among persons, and between humans and nature.